Exploring Opportunities and Challenges in Improving Campus Education and Fostering Independence - Fadllurrohman; Winarti; Mista, Hunaidah; Ma'rifah, Iza; Zubaida, Dede (Al-Qalam Institue, 2025)
Islamic Religious Higher Education Institutions (PTKI) in Indonesia face significant challenges in enhancing their competitiveness, independence, and adaptation to global educational changes. PTKI must address the gap between the global education system and their limited internal capacity, such as limited funding, inadequate infrastructure, and a shortage of skilled human resources. This study aims to develop a comprehensive governance model for PTKI that integrates academic autonomy, digital transformation, and strategic partnerships to enhance their global competitiveness. The research method used is a qualitative descriptive-analytical approach with case studies. The results show that BLU status provides flexibility in resource management, but challenges remain in integrating Islamic values ​​with the demands of educational modernization. This study concludes that PTKI must strengthen academic autonomy and seek sustainable financing models to achieve independence. The contribution of this research is to provide a strategic framework for the development of PTKI that balances tradition and modernity.